Genome‐wide analysis of DNA copy number alterations in early and advanced gastric cancers. Issue 2 (24th August 2016) - Arakawa, Noriyuki; Sugai, Tamotsu; Habano, Wataru; Eizuka, Makoto; Sugimoto, Ryo; Akasaka, Risaburo; Toya, Yosuke; Yamamoto, Eiichiro; Koeda, Keisuke; Sasaki, Akira; Matsumoto, Takayuki; Suzuki, Hiromu
Abstract : To better understand progressive changes in gastric cancer (GC), early and advanced GCs (EGC and AGC, respectively) were examined for copy number alterations (CNAs). A crypt isolation method was used to isolate DNA from tumors and normal glands in 20 AGCs, and fresh tumor samples were obtained from 45 EGCs. We assessed CNAs for differentiated‐type GCs using an Infinium HumanCytoSNP‐12v2.1 BeadChip in EGCs and AGCs. The most frequent aberrations in EGC were gains at 8q23.3 (42.2%) and 8q23.2 (40%), and loss of heterozygosity (LOH) at 3p14.2 (24.2%), suggesting that these CNAs were involved in the development of EGC. On the other hand, the highest frequencies of gains in AGC were found at 8q24.21 (65%) and 8q24.3 (60%). The most frequent LOHs in AGC were at 11q24.3‐25, 11q23.2‐24.1, 11q14.1, and 12p11.21‐13.33, whereas that in EGC was at 3p14.2. In addition, regions of copy‐neutral LOHs in AGC were detected at 11q21, 11q13.3‐14.3, 11q11, 11p13‐15.3, 12q21.1, 12q12‐13.3 and 5q33.3‐35.1. Comparisons of gains in EGC and AGC showed significant differences at 12q22‐q23.2, 12q21.33, 11p12, 11p14.1, 12q21.31‐32.32, 3p12.3, 3p14.1, 10p15.1, 1q24.2 and 2q12.1. Copy neutral LOHs were significantly higher in AGC than in EGC at 14q32.11‐32.33, 14q21.3, 14q11.2, 5q11.2, 5q 13.3, 14q21.1‐23.2, 14q13.2‐13.3, 5q12.1‐12.3, 5q11.1, and 17p13.3. The total lengths of the CNAs were significantly greater in AGC than in EGC. We found that the pattern of CNAs in AGC was quite different from that in EGC. We suggest that increasing numbers of CNAs are associated with disease progression from EGC to AGC. © 2016 Wiley Periodicals, Inc.